Not All Those Who Wander Are Lost: Insights Into Movement Pattern of the Great Indian Bustard in the Deccan Landscape of India - Shaheer Khan; Vaijayanti Vijayaraghavan; Gautam Talukdar; R. Suresh Kumar; Bilal Habib (Ecology and Evolution)
ABSTRACT Understanding animal movement patterns, such as daily foraging, seasonal migration, dispersal and other movement behaviours, is essential for effectively managing and conserving species. The Great Indian Bustard (Ardeotis nigriceps), a critically endangered bird, is thought to move opportunistically in response to environmental changes, particularly rainfall events, which influence food availability and habitat productivity. This research represents the first fine‐scale analysis of the movement behaviour of this species. In this study, we investigated the daily movements, seasonal movement variations and utilization distributions of a sub‐adult Great Indian Bustard. Over the study period, a sub‐adult travelled a total distance of 2208.62 km, with an hourly movement of 0.33 km/h (range: 0–10.4 km/h) and an average daily movement of 5.39 km. The highest daily displacement was found in summer (6.17 km/day; range: 0.26–38.99), followed by winter (5.39 km/day; range: 0.24–28.12) and the lowest was in post‐monsoon (3.15 km/day; range: 0.17–11.49). The bird consistently followed a Lévy flight movement pattern, with a scaling exponent (μ) of 2.1, both overall and across different seasons. The core areas of use (50% Kernel Density Estimates; KDE) covered 2633.07 km2, forming four distinct clusters, while the extensive utilization area (95% KDE) covered 12,080.78 km2. We identified 10 movement clusters within different regions of Maharashtra and Karnataka, which were predominantly composed of open lands, followed by Kharif crop fields and mixed crops. The mean Normalized Difference Vegetation Index (NDVI) value for these clusters was 0.31, ranging from 0.16 to 0.43, emphasizing the significance of specific vegetation cover that offers both protection and food. This study provides baseline information on the movement ecology of the Great Indian Bustard and offers valuable insights for developing more effective conservation and management strategies for this species.